STUDI PENGARUH PERUBAHAN TATA GUNA LAHAN TERHADAP INFRASTRUKTUR JARINGAN DRAINASE KOTA RANTEPAO - Sriwati, Meny (FORUM BANGUNAN, 2014)
This study aimed (1) Analyze changes in land use Rantepao Town area. (2) Analyze the influence of land use changes and their impact on existing drainage in the Rantepao Town area. The research was conducted from May to July 2011 at Rantepao, NorthÂ  Toraja regency, the study used are observation / measurement in the field, questionnaires, and data documents. This was intended to obtain data from relevant institutions or offices. The results of this study reveal that changes in land use of land in Rantepao are strongly influenced by the function of land in paddy field area, as well as garden areas that has been changed in to settlement areas. This influences the pattern of utilization system. These changes directly affect the drainage network due to the number of settlements. And it has an impact show by the increase of flood discharge plan (Q) in the region.Keywords: change in the Use of land, drainage networks